TRILOBITES ORDOVICICOS DE LA COMARCA DE JACHAL, PRECORDILLERA ARGENTINA. 1. TELEPHINIDAE (Ameghiniana, 2013)
"This is the first contribution to the knowledge of a new trilobite fauna found in shales and limestones deposited in conformity over San Juan Fm. at southwest Jáchal, San Juan province. The fauna comes from Los Blanquitos hills, in the profils of Los Pozos, Tupe and Las Aguaditas ravines. This fauna is generally silicified and in a good conservation condition. The cleaning, extraction and photographic techniques of the samples are described. The mentioned forms described in this paper belongs to the Family Telephinidae, genus Telephina (Telephina). Six new species are described: T. (T.) frontistriata, T. (T.) rectisulcata, T. (T.) feiini, T. (T.) alejandrina, T. (T.) aguaditensis and T. (T.) argentina. The stratigraphic distribution range of each form was determined into the ordovician sequence of Jáchal.This first occurrence of Telephinidae in South America appoints the definitively widespread of the Family."